Dominasi Tingkat Bunga Penjaminan LPS terhadap BI-Rate dalam Penentuan Suku Bunga Perbankan di Indonesia - Muhammad sahirul Alim; Dina Fareza; Tri Antoro Adi; Aqiela Azzahra (Riviera Publishing, 2025)
Indonesia’s financial stability is highly dependent on the effectiveness of monetary policy transmission through the interest rate channel. Two key benchmark instruments are Bank Indonesia’s policy rate (BI-Rate/BI-7DRR) and the Deposit Insurance Corporation’s (LPS) guaranteed interest rate. Both play a role in shaping banks’ behavior toward deposit and lending rates, yet empirical evidence on which instrument is more dominant remains varied. This study aims to examine the influence of the BI-Rate and the LPS guaranteed rate on deposit and lending rates in Indonesia. The method used is path analysis with secondary data from official publications of BI, OJK, and LPS for the 2019–2024 period. The analysis employs STATA with a 5 percent significance level. Independent variables consist of the BI-Rate and the LPS guaranteed rate, while the dependent variables are term deposit rates and lending rates. The results indicate that the BI-Rate does not have a significant effect on either deposit or lending rates. In contrast, the LPS guaranteed rate has a positive and significant effect on both variables. These findings suggest that LPS policy plays a more decisive role in bank funding pricing. The main implication of this research is the need for synchronization between BI and LPS policies so that monetary transmission to the real sector can become more effective.